Availability of dental services for people with hearing impairments: communication between doctor and patient - Vitaly Lytovchenko; Svitlana Lytovchenko (Bogomolets National Medical University, 2021)
The article presents modern requirements for the provision of medical care in the context of a socio-cultural approach, in which restrictions are seen as the result of discrimination by society, not the human condition. The concept of "universal design" in all spheres of human life acquires special significance. The deaf community is seen as a linguistic and cultural minority with its own language (sign language) and culture (deaf culture), so it is very important to offer solutions and approaches to establish quality communication between sign language patients and doctors, junior medical staff and thus ensure an inclusive approach. in the field of health care. Given the urgency of the problem, the aim of the article is to analyze the theoretical and clinical aspects of the problem of accessibility of medical (dental) services for patients with severe hearing impairment (sign language) and identify effective methods to meet their special communication needs. Methods of theoretical analysis of literature sources and results of modern research presented in electronic scientific publications included in scientometric databases PubMed, Index Copernicus, Ulrich's Periodicals, Google Scholar, Web of Science, Scopus, Medline, etc .; examination, treatment and counseling of a sign language patient within the framework of surgical preparation for orthopedic prosthetics on the basis of the Department of Surgical Dentistry and Maxillofacial Surgery of NMU named after OO Worshipers. The results of the study give grounds to draw the following conclusions: analysis of professional literature, clinical cases indicate the urgency of the problem of communication of deaf (sign language) patients and dentists, setting benchmarks for reforming the health care system in accordance with modern socio-cultural approaches; the main methods of communication between a dentist and a patient with severe hearing impairment are characterized: through a sign language interpreter; by means of written speech; by using a jotting-algorithm with gestures required during standard dental manipulations; determined that the use of the jotting-algorithm promotes effective communication with sign language patients, taking into account the peculiarities of the dentist and the special communication needs of such patients.